2016
DOI: 10.1513/annalsats.201510-701oc
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Noninvasive and Invasive Ventilation in Patients Hospitalized with Asthma Exacerbation

Abstract: Rationale: Little is known about the effectiveness of noninvasive ventilation for patients hospitalized with asthma exacerbation.Objectives: To assess clinical outcomes of noninvasive (NIV) and invasive mechanical ventilation (IMV) and examine predictors for NIV use in patients hospitalized with asthma.Methods: This was a retrospective cohort study at 97 U.S. hospitals using an electronic medical record database. We developed a hierarchical regression model to identify factors associated with the choice of ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
5
29
0
5
Order By: Relevance
“…21,22 However, an American database study had similar LOS for their NIV patients of 4.1 days. 15 Our blood gas data was consistent with severe asthma and the median pH is lower than other studies. 21,26 Previous studies have also shown that NIV is effective in decreasing arterial carbon dioxide in severe asthma and can be as effective as IMV.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…21,22 However, an American database study had similar LOS for their NIV patients of 4.1 days. 15 Our blood gas data was consistent with severe asthma and the median pH is lower than other studies. 21,26 Previous studies have also shown that NIV is effective in decreasing arterial carbon dioxide in severe asthma and can be as effective as IMV.…”
Section: Discussionsupporting
confidence: 90%
“…Our failure rate for NIV was 4.5%, similar to a large American retrospective cohort from an electronic medical record database but less than other studies . Leatherman reports a failure rate of 17% across five studies .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In a recent retrospective cohort study [59] conducted in 97 US hospitals during a 4-year period, the use of NIV in patients with acute asthma was 4% (556 out of 13 930) and the use of invasive ventilation was 5% (668 out of 13 930). Failure rate (defined as intubation) of NIV was 4.7% (26 patients).…”
Section: Recommendationmentioning
confidence: 99%